2011
DOI: 10.1590/s1516-635x2011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography applied to the evaluation of metabolic heat loss of chicks fed with different energy densities

Abstract: Brazil must comply with international quality standards and animal welfare requirements in order to maintain its position as world's largest exporter of poultry meat. With the scenario of global climate change there is the forecast of occurrence of extreme events with characteristics of both excess cold and heat for several regions of the country. This study aimed to evaluate the effectiveness of using images of infrared thermography to evaluate the loss of sensible heat in young broilers fed different dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 19 publications
0
26
0
7
Order By: Relevance
“…This study is the first attempt to our knowledge to estimate the heritability of body temperature measured by infrared thermography in poultry. Infrared thermal imaging has undergone major development during the past decade for application to biological research into thermal physiology in mammals (Klir and Heath, 1992) and chickens (Nääs et al, 2010;Ferreira et al, 2011). Using infrared thermography, Yahav and Giloh (2012) demonstrated that the main skin zones of heat dissipation were the head (including comb and barbs), the shank and, to a lesser extent, the wing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first attempt to our knowledge to estimate the heritability of body temperature measured by infrared thermography in poultry. Infrared thermal imaging has undergone major development during the past decade for application to biological research into thermal physiology in mammals (Klir and Heath, 1992) and chickens (Nääs et al, 2010;Ferreira et al, 2011). Using infrared thermography, Yahav and Giloh (2012) demonstrated that the main skin zones of heat dissipation were the head (including comb and barbs), the shank and, to a lesser extent, the wing.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared thermography has in recent years become a valuable tool in veterinary and animal sciences to measure infrared body radiation to detect fluctuations in body surface temperature (Stewart et al, 2005;McCafferty, 2007;Ferreira et al, 2011). The advantage of this technique is that it is noninvasive and of remote assessment, and can measure body surface temperature with minimal manipulation of birds that can bias measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Em outro estudo foi analisada a eficiência do aparelho termográfico na detecção da variação de produção de calor metabólico de pintos na fase de crescimento. Esses animais foram alimentados com diferentes densidades energéticas, de modo que foi verificado que a termografia por infravermelho identificou efetivamente a atividade metabólica dessas aves (FERREIRA et al, 2011).…”
Section: Animais De Produçãounclassified
“…Through this, we may state that thermography is a valid tool to observe animal skin temperatures under various conditions, as a non-invasive method. According to BUSTOS MAC-LEAN (2012), D' ALTERIO et al (2011), FERREIRA et al (2011), MOURA et al (2011), NÄÄS et al (2010) and SCOLARI et al (2009, this technique has advantages over conventional methods. Moreover, ZOTTI (2010) reported that errors can be minimized by the use of such device, beyond of providing high precision and accurate records, as well as convenience for data manipulation and temperature measurements .…”
Section: Through Thermographic Images Inmentioning
confidence: 99%